Cellulose in situ Decomposition in a Bog Exposed to Increasing Nitrogen Treatments, 2012-2014 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). We examined the effects of N addition on cellulose placed in the bog from 2012-2014 and collected after 5 and 17 months. Decomposition of cellulose filter paper in surface peat increased with N input. Water addition alone had no significant effect on exponential decay constants ( k values). In control and 0 kg ha -1 yr -1 treatments, k values averaged 0.58 yr -1 , corresponding to 42% of initial mass lost in the first year, while in the 25 kg ha -1 yr -1 treatment, k values averaged 1.27 yr -1 , corresponding to 72% of initial mass lost in the first year. Assessment of decomposition and its controls may be especially important in peatlands, as the development and persistence of peat depends on an excess of NPP over decomposition throughout the peat profile. There is some evidence that increasing N deposition/availability stimulates cellulose decomposition in surface bog peat, as we found at Mariana Lakes Bog.